(untitled) (De Rebus Antiquis, 2020)
The article presents Italian translation and commentary of Gortyn ‘code’ columns X.33-XII.23 about adoption’s legal dispositions. The epigraphic text is compared with literary sources of Athenian law in classical age, pointing out analogies and variances. The more substantial difference is that in Gortyn’s law the adoptive son had less prerogatives, in accordance with an archaic and aristocratic society.